Review of Egogepa Razowski, with description of a new species (Lepidoptera: Tortricidae) - Wang, Xinpu; Li, Houhun (Zootaxa, 2006)
The genus Egogepa Razowski is reviewed, and one new species is described: Egogepa crassata sp. n. The adult and male genitalia of the new species are illustrated, and a key to the known species of the genus is included.